2016
DOI: 10.1681/asn.2016020132
|View full text |Cite
|
Sign up to set email alerts
|

Oxalobacter formigenes–Derived Bioactive Factors Stimulate Oxalate Transport by Intestinal Epithelial Cells

Abstract: Hyperoxaluria is a major risk factor for kidney stones and has no specific therapy, although colonization is associated with reduced stone risk. interacts with colonic epithelium and induces colonic oxalate secretion, thereby reducing urinary oxalate excretion, an unknown secretagogue. The difficulties in sustaining colonization underscore the need to identify the derived factors inducing colonic oxalate secretion. We therefore evaluated the effects of culture conditioned medium (CM) on apical C-oxalate uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 70 publications
4
63
2
3
Order By: Relevance
“…We present the first comprehensive study of human oxalate-degrading microbes, with multi-omics evidence, and quantitatively characterized their contributions. Our finding that multiple human gut microbes encode ODPs is consistent with multiple prior studies [22,43,64,80,81] [31,88,89] for direct bacterial access.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We present the first comprehensive study of human oxalate-degrading microbes, with multi-omics evidence, and quantitatively characterized their contributions. Our finding that multiple human gut microbes encode ODPs is consistent with multiple prior studies [22,43,64,80,81] [31,88,89] for direct bacterial access.…”
Section: Discussionsupporting
confidence: 91%
“…Multiple gut microbes can degrade oxalate [22], including Oxalobacter formigenes, an oxalate autotroph [23][24][25][26][27]. When given to animals, O. formigenes has reduced host oxalate burden [28][29][30][31][32][33]. [44][45][46].…”
Section: Mainmentioning
confidence: 99%
“…A confounding issue is the oxalate-degrading activity of Oxalobacter enzymes and degradation of the 14 C-oxalate tracer used to measure intestinal fluxes together with the highly oxygenated buffers used in Ussing chamber experiments [7]. A number of intriguing recent reports have shown that exposure to Oxalobacter conditioned media (CM) at a 1:50 dilution for 6–24 h stimulates oxalate influx by Caco-2 cells and a > 4-fold increase in DRA mRNA expression, with no changes to DTDST or PAT1 [170, 171]. We repeated this experiment measuring unidirectional oxalate fluxes across Caco-2 monolayers in Ussing chambers using a 1:50 dilution (and also a 1:25 dilution; see Supplementary Table 1) of CM from the cultured human strain of Oxalobacter , HC-1.…”
Section: Gut Microbiota and Oxalate Homeostasismentioning
confidence: 99%
“…6). In addition to these contrasting results, it is difficult to reconcile why Oxalobacter CM targets DRA [170, 171], and not PAT1, since the latter is the major oxalate transporter in Caco-2 cells [47], and given the respective contributions of PAT1 and DRA to oxalate secretion and absorption in mice [1618]. It is also notable that Hassan et al reported no effect of CM from Lactobacillus acidophilus [170, 171], whereas several studies have previously shown that Lactobacillus significantly upregulates the functional expression of DRA in both Caco-2 and mouse models [172174].…”
Section: Gut Microbiota and Oxalate Homeostasismentioning
confidence: 99%
“…While the responsible molecule has not yet been identified, culture media exposed to Oxf , administered rectally to knockout mice with primary hyperoxaluria type 1, reduced urinary oxalate excretion (>32.5%) and stimulated distal colonic oxalate secretion (>42%) in Ussing chamber-mounted bowel cross-sections [29]. The mechanism of action included activation of the SLC26A6 transporter by protein kinase A without any increased expression of the protein.…”
Section: Animal Studiesmentioning
confidence: 99%